Mangrove Vegetation Analysis in Mangrove Ecosystems in the Coastal Area of Bazartete, Liquica District Timor-Leste - Tilman, Efrem; Santoso, Nyoto; Soekmadi, Rinekso (Department of Forest Resources Conservation and Ecotourism - IPB University, 2024)
Mangroves are important ecosystems that provide a range of ecosystem functions and services that support livelihoods and the environment. Mangrove forests in Timor-Leste have been exploited since at least the 1940s for agriculture, timber, and clearing for settlements. Measurement of the distribution of mangrove vegetation was carried out at two observation stations, namely: Station I, located in Tibar Village; Station II and located in Ulmera Village. The determination of the research location was determined by purposive sampling after a survey was conducted. The results of vegetation analysis that has been done there are 4 types of mangroves found such as; Sonneratia alba, Rhizophora apiculata, Rhizophora mucronata and Brugueira cylindrica. Stand density at Tibar station is dominated by the type of Sonneratia alba having a density of 366.67 trees / ha with a species mastery level of 91.23 m2 / ha and has an INP value of 219.98%. In contrast to the results of observations in Tibar village, the density of stands at the Ulmera observation station, the Rhizophora apiculata species has a higher density of 511 trees/ha but the level of species mastery is dominated by the Sonneratia alba species of 53 m2/ha with INP = 116%. The density level is dominated by the Rhizophora apiculata species because in the middle zone the substrate is muddy, while in the outer zone directly facing the sea and always inundated with sea water, more Sonneratia alba species are found. Key words: bird, community, diversity, mine, reclamation